Emotions and negativity - Humphrey, Ronald H.; Ashkanasy, Neal M.; Troth, Ashlea C. (Research on emotion in organizations ;, 2022)
The focus of Volume 17 of Research on Emotion in Organizations is on how negative emotions at work can be intense due to a myriad of reasons including feelings of failure, rejection, job insecurity, stressful work demands and poor coping strategies. The chapters in this book address some of the more frequent and vexing problems and resulting negative emotions that can occur at work. Many of these chapters explore relatively under-researched topics, and thus the potential for their future impact on research is enormous. Many of these topics are under-researched despite the emotions they address having a major impact on people's lives. With an emphasis on negative emotions, coping strategies, emotional regulation, emotional labor, management and leadership, chapter authors detail a wide-ranging set of means to ameliorate negative emotions in organizational settings. These solutions, based on state-of the-art research, will be of immense help to workers and leaders as they face the challenges of the modern workplace. In addition, they should help guide human resource management training and development programs.